2012
DOI: 10.1371/journal.pone.0033403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blood Products on Inflammatory Response in Endothelial Cells In Vitro

Abstract: Background Transfusing blood products may induce inflammatory reactions within the vascular compartment potentially leading to a systemic inflammatory response. Experiments were designed to assess the inflammatory potential of different blood products in an endothelial cell-based in vitro model and to compare baseline levels of potentially activating substances in transfusion products. Methods The inflammatory response from pre-activated (endotoxin-stimulated) and non-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 38 publications
1
25
1
1
Order By: Relevance
“…Our findings of significant increases in proinflammatory cytokines after transfusion are in keeping with both in vitro evidence for induction of pro-and anti-inflammatory cytokines following PRBC exposure (18,19) and adult in vivo data (20). Specifically, PRBC transfusion has been demonstrated to result in significant increases in TNF-α (19) and IL-8 (21). We observed significant increases in plasma IL-1β, IL-8, TNF-α, and MCP-1.…”
Section: Discussionsupporting
confidence: 86%
“…Our findings of significant increases in proinflammatory cytokines after transfusion are in keeping with both in vitro evidence for induction of pro-and anti-inflammatory cytokines following PRBC exposure (18,19) and adult in vivo data (20). Specifically, PRBC transfusion has been demonstrated to result in significant increases in TNF-α (19) and IL-8 (21). We observed significant increases in plasma IL-1β, IL-8, TNF-α, and MCP-1.…”
Section: Discussionsupporting
confidence: 86%
“…The risk and extent of peri-and postoperative bleeding depends on various factors, e.g., preexisting diseases, congenital or acquired coagulation disorders and their management as well as the surgical procedure itself [31]. If perioperative bleeding occurs, the risk of associated morbidity and mortality increases [29,30,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still many blood transfusion associated complications, like hemolysis, fever, allergy, immunosuppression and infectious diseases induced by virus and bacteria, etc.. As early as 1970s, studies have showed that homologous blood transfusion can lead to blood-transfusion connected immunosuppression (Opelzet al, 1973) and prei-operative blood transfusion can increase the recurrence rate of tumors (Amato et al, 2006). It is estimated that about 0.2% blood receptors have showed inflammatory responses marked by systematic inflammatory response syndrome due to blood transfusion, which can trigger serious septicemia, lung failure and multiple organ failures (Urner et al, 2012). Therefore, blood protection technique receives more and more attentions recently.…”
Section: Influence Of Autologous and Homologous Blood Transfusion On mentioning
confidence: 99%